Enhancements in E-government using New Technologies and Approaches - Maryam Aboud (المجلة الدولية للحاسبات والمعلوماتية, 2024)
E-Government aims to provide required services to required users at the required time. E-government uses Information and Communication technologies (ICT) to provide essential government services and information exchange with the citizens and other stakeholders through the internet. Existing e-government faces many challenges, from development to implementation. The objective of this paper is to give insights about cloud computing, agile principles and how to use them for E-government. This paper reviews different cloud computing and agile development methodologies with new technologies that have come with new approaches.